Dinâmica de uma assembleia de palmeiras e sua relação com a topografia em floresta de terra firme na Amazônia Central - Melo Neto, Paulo Rodrigues de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2024)
In recent years, several studies have reported changes in the structure of different taxonomic groups in mature tropical forests free of apparent environmental disturbances. The phenomenon may be explained by the oscillations of the climatic patterns that have become much more frequent in the last decades. However, local aspects like topography may mitigate such effects. Considering these factors , we analyzed the long term dynamics of an assemblage of palm species in a 10 ha permanent plot in a continuous a nd mature forest of the Biological Dynamics of Forest Fragments Project (BDFFP), Central Amazon. A previous census of adult palm was realized in 1990 and again in 2020. All palms were marked, classified according to their position in the forest strata, and identified. Thus, we evaluated the dynamics of the assembly in general and by strata, considering abundance, composition, and beta diversity, as well as the population dynamics of the species. All parameters were related to topography. The survey recorded 33 palm species, three more species than in 1990, and an impressive and general increase in diversity . Even with 1/3 of mortality, the net increase of the assembly was almost 50%, revealing a dramatic change in density from around 650 to almost 1,000 adul t palms/ha. Mortality was more significant among the tree palm species or the sub canopy palms. Meanwhile, the forest's understory presented the highest diversity of species. Species gain over time drove the changes in the assemblage composition. Regarding topography, the elevation aspect influenced the species' distribution, while the terrain's slope affected the assemblage dynamics. In conclusion, from continuous and protected forests, palm assemblage changing patterns following other taxonomic groups cor roborate that such changes may be related to extreme climatic events that have affected the Amazon in recent decades.
Dynamics of the palm assembly and its relationship with topography in terra firme forest in the Central Amazon
Keywords: Arecaceae; Abundância; Dinâmica florestal; Ecologia de Comunidades; Monitoramento; Mudanças Direcionais; PDBFF; Floresta Tropical